2015
DOI: 10.1177/0284185113519775
|View full text |Cite
|
Sign up to set email alerts
|

MR image texture in Parkinson’s disease: a longitudinal study

Abstract: Texture analysis offers a quantitative method for detecting structural changes in brain MR images. However, the protocol and repeatability of the method must be enhanced before possible clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 34 publications
(43 reference statements)
1
13
0
Order By: Relevance
“…TA may also prove useful to assess disease progression; this was shown in a longitudinal study with Parkinson disease patients where authors found progressive texture abnormalities at both thalami, caudate, and putamen that correlated with clinical deterioration. 23 As previously mentioned, we found only one other study using TA in ALS (https://www.cs.ualberta. ca/research/theses-publications/technical-reports/2014/TR14-01), which also found significant changes in ALS patients compared to controls.…”
Section: Discussionmentioning
confidence: 90%
“…TA may also prove useful to assess disease progression; this was shown in a longitudinal study with Parkinson disease patients where authors found progressive texture abnormalities at both thalami, caudate, and putamen that correlated with clinical deterioration. 23 As previously mentioned, we found only one other study using TA in ALS (https://www.cs.ualberta. ca/research/theses-publications/technical-reports/2014/TR14-01), which also found significant changes in ALS patients compared to controls.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, pathological and DTI studies have demonstrated the presence of Lewy body deposits and microstructural deficits in the neostriatum of PD patients (4,7,8,41). All of these microstructural changes might be characterized by alteration of textural patterns of T2W images (28) and captured by radiomics approach.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies indicated that radiomics features derived from DAT SPECT images can serve as a biomarker for PD progression tracking (26,27). Notably, a previous texture analysis study demonstrated that texture features based on T2-weighted imaging (T2WI) differed between PD patients and healthy controls in many brain regions (28). However, there is no published study that investigated the diagnosis of PD on conventional MRI by using a radiomics approach.…”
Section: Introductionmentioning
confidence: 99%
“…However the real utility of these texture features might be related to the evolution of the disease and, therefore, its application in longitudinal studies, as it has been recently proven [19]. It is very convenient to use a single number to characterize a measure (in our case, texture features) in each direction.…”
Section: Discussionmentioning
confidence: 99%
“…To complement the methodology, along with the intensity levels in the path, we have developed a radial method to compute the Gray Level Co-occurrence Matrix (GLCM). Firstly developed by Haralick [18], the GLCM is one of the preferred methods to characterize the texture of 2D images, and have been successfully used in the characterization of brain images [15,19]. In our approach, the original algorithm is modified to compute the GLCM along the extracted curvilinear paths and its neighbourhood, from which a number of descriptors of the underlying texture in each direction can be extracted.…”
Section: Introductionmentioning
confidence: 99%